IMPROVING THE TECHNOLOGIES FOR SORTING 6-7-YEAR-OLD CHILDREN INTO SPORTS CATEGORIES (European Journal of Interdisciplinary Research and Development, 2023)
The article "Developing Competence in Sorting Children into Sports Using Technology" focuses on the use of technology to improve the process of sorting children into different sports. The article discusses the challenges faced by physical education teachers in accurately identifying a child's potential in a particular sport and proposes the use of technology-based assessment tools as a solution. The article provides an overview of various technology-based assessment tools that can be used, including video analysis, wearable sensors, and machine learning algorithms. The effectiveness of these tools is discussed, along with their potential benefits and limitations.